Influenza Vaccination Behavior and Media Reporting of Adverse Events - Ylenia Brilli; Claudio Lucifora; Antonio Russo; Marco Tonello (Institute of Labor Economics (IZA), 2020)
We study the role of media reporting of alleged adverse effects of influenza vaccination on adults' (aged 50 or more) decisions to vaccinate against the flu. We exploit the diffusion of news linking suspected deaths to the vaccine, during the 2014 vaccination campaign in Italy. Using daily variation in news items across the 2014 campaign and the previous year campaign, unaffected by media cases, we show that media reporting decreases flu vaccination by about 2.5% (78 fewer vaccinations per day). The effect, however, is short-lived, as it fades away after approximately 10 days from the news outbreak.
Keywords: I12; I18; J10; 330; influenza; vaccination; mass media